Comparative analysis of Islamic and conventional banking financing in Indonesia, January 2003 - October 2015 - Lina Nugraha Rani; Eko Fajar Cahyono (Department of Islamic Economics, Islamic University of Indonesia, 2017)
Islamic and conventional banks are in the same banking competitive industry. This study examined the comparison between the effects of external and internal factors on the bank's financing problems (NPF with NPL), with the period January 2003 - October 2015. External factors comprise of economic performance (EK), inflation (INF) and the global financial crisis dummy (D07). Meanwhile, internal factors consist of financing (FIN / LOAN) and the financing rate of return (FR). The results of cointegration test indicated that there was a long-term relationship between the external and internal factors of banks’ NPF and NPL. The results of research in general shows that external factors significantly affect the bank's NPL but not the NPF. Internal factors of the bank had a negative effect on NPF and higher influence than the NPL. This suggests that the increase in financing rate of return of Islamic banks lower the NPF. It is concluded that the financing of Islamic banks is healthier compared to that of conventional banks.